The Impact of STEAM Learning with Loose Parts on the Cognitive and Artistic Development of Children Aged 5-6 Years - Isnariyati, Eny; Khotimah, Nurul; Setyowati, Sri; Hasibuan, Rachma; Matheos Lasarus Malaikosa, Yes; Fitri, Ruqoyyah (Journal of Islamic Education Students (JIES), 2025)
This study aims to analyze the effect of STEAM learning using Loose Parts on the cognitive and artistic abilities of children aged 5-6 years. The research employs a quantitative approach with a Quasi-Experimental Design. The subjects consist of 48 children divided into experimental and control groups. Hypothesis testing was conducted using the Mann-Whitney U Test, yielding a p-value of < 0.001 (α = 0.05), indicating a significant difference between the two groups. The findings confirm that STEAM learning with Loose Parts has a positive impact on enhancing young children's cognitive and artistic abilities. This approach not only stimulates creativity and problem-solving skills but also improves logical thinking and artistic expression. Therefore, integrating Loose Parts into STEAM learning can be an effective strategy for optimizing early childhood development.